Roles for Rice Membrane Dynamics and Plasmodesmata during Biotrophic Invasion by the Blast Fungus - Kankanala, Prasanna (American Society of Plant Biologists, 2007)
Rice blast disease is caused by the hemibiotrophic fungus Magnaporthe oryzae, which invades living plant cells using intracellular invasive hyphae (IH) that grow from one cell to the next. The cellular and molecular processes by which this occurs are not understood. We applied live-cell imaging to characterize the spatial and temporal development of IH and plant responses inside successively invaded rice (Oryza sativa) cells. Loading experiments with the endocytotic tracker FM4-64 showed dynamic plant membranes around IH. IH were sealed in a plant membrane, termed the extra-invasive hyphal membrane (EIHM), which showed multiple connections to peripheral rice cell membranes. The IH switched between pseudohyphal and filamentous growth. Successive cell invasions were biotrophic, although each invaded cell appeared to have lost viability when the fungus moved into adjacent cells. EIHM formed distinct membrane caps at the tips of IH that initially grew in neighboring cells. Time-lapse imaging showed IH scanning plant cell walls before crossing, and transmission electron microscopy showed IH preferentially contacting or crossing cell walls at pit fields. This and additional evidence strongly suggest that IH co-opt plasmodesmata for cell-to-cell movement. Analysis of biotrophic blast invasion will significantly contribute to our understanding of normal plant processes and allow the characterization of secreted fungal effectors that affect these processes.